Trace of the Kerguelen mantle plume: Evidence from seamounts between the Kerguelen Archipelago and Heard Island, Indian Ocean - Weis, D; Frey, Fa; Schlich, R; Schaming, M; Montigny, R; Damasceno, D; Mattielli, N; Nicolaysen, Ke; Scoates, Js (Geochemistry, Geophysics, Geosystems, 2002)
The gravity and bathymetric highs on the Kerguelen Plateau in the southern Indian Ocean between the Kerguelen Archipelago and Heard Island are seamounts formed of Miocene alkalic basalts similar to those found on the islands. Dredging during the Kerimis survey cruise recovered >1 ton of mostly basaltic rocks. One of the dredges (D6) yielded a large volume of in situ alkalic picritic pillow basalts, the first picritic lavas recovered that are related to the Kerguelen plume. K-Ar and Ar-40-Ar-39 ages are between 18 and 21 Ma for all but one sample, and these ages are only slightly younger than the main phase of volcanism on the archipelago. The dredged lavas form three distinct groups based on chemical and isotopic compositions. Incompatible element abundance ratios overlap with compositional groups defined by lavas from both the Kerguelen Archipelago and Heard Island indicating that alkalic volcanism in this region of the Kerguelen Plateau has been spatially diverse. Olivine and picritic basalts have Sr and Nd isotopic characteristics similar to most of the lavas exposed on the archipelago and those proposed for the Kerguelen plume. However, compared to Kerguelen Archipelago lavas, the picritic basalts have relatively low Pb-206/Pb-204 which is a characteristic of Cretaceous basalt forming some parts of the Kerguelen Plateau. We propose that the apparent age trend of the lavas from 34 Ma in the Northern Kerguelen Plateau (ODP Leg 183, Site 1140) to 24-30 Ma on the Kerguelen Archipelago to 18-21 Ma on the dredged submarine volcanoes, and even possibly to recent volcanism on Heard and McDonald Islands, may correspond to the Tertiary hot spot track of the Kerguelen plume.